Study of Force Changes Based on Orthotic Elements Under the First Ray - Marina Ballesteros-Mora; Pedro V. Munuera-Martínez; Natalia Tovaruela-Carrión; Antonia Sáez-Díaz; Javier Ramos-Ortega (Applied Sciences)
The first ray plays a fundamental role in foot biomechanics, particularly in stabilizing the medial longitudinal arch and enabling efficient weight transfer during the mid-stance and propulsion phases of gait. When dorsiflexed—a condition known as metatarsus primus elevatus—especially in its flexible form, this structure disrupts load distribution, impairs propulsion, and contributes to various clinical symptoms. Despite its clinical importance, the biomechanical impact of orthotic elements placed beneath the first ray remains underexplored. This study aimed to quantify the variations in medio-lateral (Fx), antero-posterior (Fy), and vertical (Fz) force vectors generated during gait in response to different orthotic elements positioned under the first ray. A quasi-experimental, post-test design was conducted involving 22 participants (10 men and 12 women) diagnosed with flexible metatarsus primus elevatus. Each participant was evaluated using custom-made insoles incorporating various orthotic elements, while gait data were collected using a dynamometric platform during the mid-stance and propulsion phases. Significant gait-phase-dependent force alterations were observed. A cut-out (E) reduced medio-lateral forces during propulsion (p < 0.05), while a kinetic wedge (F) was correlated with late-stance stability (r = −0.526). The foot posture index (FPI)/body mass index (BMI) mediated the vertical forces. The effect sizes reached 0.45–0.42 for antero-posterior force modulation. Phase-targeted orthoses (a cut-out for propulsion, a kinetic wedge for late stance) and patient factors (FPI/BMI) appear to promote biomechanical efficacy in metatarsus primus elevatus, enabling personalized therapeutic strategies.